2016
DOI: 10.1038/ncomms13715
|View full text |Cite
|
Sign up to set email alerts
|

A programmable DNA origami nanospring that reveals force-induced adjacent binding of myosin VI heads

Abstract: Mechanosensitive biological nanomachines such as motor proteins and ion channels regulate diverse cellular behaviour. Combined optical trapping with single-molecule fluorescence imaging provides a powerful methodology to clearly characterize the mechanoresponse, structural dynamics and stability of such nanomachines. However, this system requires complicated experimental geometry, preparation and optics, and is limited by low data-acquisition efficiency. Here we develop a programmable DNA origami nanospring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 48 publications
0
78
0
1
Order By: Relevance
“…Here, to overcome the limitation of conventional approaches, we engineered thick filaments using three-dimensional DNA origami [28][29][30] and recombinant human myosin II 31 (Fig. 1b).…”
mentioning
confidence: 99%
“…Here, to overcome the limitation of conventional approaches, we engineered thick filaments using three-dimensional DNA origami [28][29][30] and recombinant human myosin II 31 (Fig. 1b).…”
mentioning
confidence: 99%
“…Similarly to lipid nanotechnology, DNA nanotechnology has allowed for the study of protein systems with unprecedented precision. For example, in recent work, a DNA nanospring was used as a force sensor to make direct single-step observations of the cellular protein motors Myosin V and Myosin VI under load, confirming for the first time that the stepping behaviour of these motors depends on the force applied to them [86]. However, this technology also has limitations.…”
Section: Limitations Of Dna Nanotechnologymentioning
confidence: 92%
“…From this perspective the development of bio-based nanomaterials, produced from the programmed assembly of biomolecules as DNA, RNA, and proteins, offers novel tools to analyse and control the spatiotemporal properties of molecular and cellular processes, but also to engineer novel synthetic functionalities 7 , 8 . For instance, DNA-based scaffolds, which provide very precise biomolecule spatial positioning, have been used to elucidate biophysical mechanisms underlying cytoskeleton motor activity 9 11 or as fluorescent biosensors to probe the internal environment of living cells 12 , 13 . Complementary, pioneer studies have demonstrated how synthetic protein scaffolds can modulate the cooperativity of ensembles of molecular motors 14 , and artificially control metabolic flux 15 or signalling pathways 16 18 .…”
Section: Introductionmentioning
confidence: 99%